DEFEK TRABECULAR MESHWORK OLEH MUTASI GEN CYP1B1 PADA PATOGENESIS GLAUKOMA KONGENITAL PRIMER - Agverianti, Theodora; Samosir, Renti Kusumaningrum; Theodorus, Emeraldha; Valentina, Debby Cinthya Damiri (Essence of Scientific Medical Journal; Vol 18 No 2 (2020): Volume 18 No. 2 (Juli - Desember 2020) Essential: Essence of Scientific Medical Journal, 2021)
Abstract Introduction: Primary congenital glaucoma is type of congenital glaucoma that often occurs. The incidence of congenital glaucoma is 1 per 10.000 births. About 65% cases of congenital glaucoma affect men. Congenital glaucoma is associated with an autosomal recessive gene. Discussion: Congenital glaucoma is glaucoma that occurs in infants or children that occurs due to congenital disorders of aqueous humor flow. This condition is usually progressive and bilateral which has the potential to damage the optic nerve. Early symptoms that can occur are epiphora, which is then followed by photophobia and enlargement of the eyeball or buphthalmos. The most important physical examination that must be done is intraocular pressure examination, visual examination which can be done by fix-and-follow method, and funduscopic examination. The most common cause of congenital glaucoma is a mutation in the CYP1B1 gene. The CYP1B1 gene plays a role in the production of several morphogens that play an important role in the development of trabecular meshwork and other components in aqueous humor secretion. Structural abnormalities caused by mutations in this gene can inhibit fluid drainage resulting in increased intraocular pressure. Another mechanism reported was the CYP1B1 mutation can cause defects in the neural crest. Conclusion: CYP1B1 gene mutation plays role in the pathophysiology of congenital glaucoma.